Влияние предварительного замораживания и низкотемпературного хранения на взаимодействие ацетилхолинэстеразы с озоном - Грищенко, В.И.; Дюбко, Т.С.; Зинченко, В.Д. (Видавничий дім "Академперіодика" НАН України, 2007)
Ozone (O₃) effect on the conformation state and the enzyme activity of acetylcholinesterase (CE) in solutions subjected to freezing by two regimes: “slow” down to −18 °C (I regime) and
“rapid” down to −196 °C (II regime) with the following storage for 1 week under corresponding temperatures has been studied by using the methods of optical pectroscopy. Freezing rate and storage temperature were established to affect the CE conformation state determining the protein sensitivity to the following ozone treatment. The enzyme samples treated according to
regime I are characterized by the highest sensitivity to increasing ozone doses. A feasible relation of sensitivity to the ozone effect of CE samples, treated according to regimes I and II, with
differences in the structure of molecular aggregates formed at the “rapid” and “slow” freezing of the enzyme solution is discussed.